Comparison of two 3-dimensional user-friendly voxel-based maxillary and 2-dimensional superimposition methods - Sheeran, Shelby; Hartsfield, James; Omami, Galal; Bazina, Mohamed (American journal of orthodontics and dentofacial orthopedics, 2023)
Cephalometric superimpositions have many uses in orthodontics, including growth evaluation and outcome assessment. However, 2-dimensional (2D) cephalograms can be distorted and yield incomplete 2D data. Cone-beam computed tomography (CBCT) imaging provides a 3-dimensional (3D), undistorted, and more complete patient analysis. CBCT imaging provides many unique advantages to the orthodontic practice and can influence how treatment outcomes are assessed. This study aimed to investigate the validity of 3D maxillary voxel-based superimpositions compared with the 2D method recommended by the American Board of Orthodontists. This retrospective study included pretreatment and posttreatment CBCT images of 30 adolescent patients. The images were superimposed using the 3D voxel-based tools in Dolphin Imaging software (Dolphin Imaging and Management Solutions, Chatsworth, Calif). Two different 3D anatomic registration areas (3DA-3DB) were tested for the validity and reproducibility of the 3D maxillary superimpositions as compared with the 2D method. Linear and angular measurements were used to evaluate the dental changes of the maxillary right central incisor and first molar. Data distribution was normal by the Shapiro-Wilk W test. A mixed model analysis of variance test was done to compare the 3 superimposition types within each subject, followed by pairwise Tukey-Kramer comparisons when indicated. After applying the Benjamini-Hochberg procedure to control the false discovery rate at 0.05 with multiple testing, the U1 vertical difference was statistically significant (P <0.0001) for the superimposition method, though the mean differences were clinically nonsignificant (0.52 mm, 0.76 mm). The U1 angular and U6 vertical differences were not statistically significant for the superimposition method (P = 0.3636 and P = 0.1863, respectively). The 3D voxel-based maxillary superimpositions showed similar results to conventional 2D superimpositions recommended by the American Board of Orthodontists. •Three-dimensional (3D) superimposition can be done with open-source or commercial software.•Dolphin 3D maxillary voxel-based superimposition is precise and reliable.•Dolphin 3D superimposition can be used in clinics with accurate results.